Azido Pentoses: A New Tool To Efficiently Label Mycobacterium tuberculosis Clinical Isolates. (29th March 2017) - Kolbe, Katharina; Möckl, Leonhard; Sohst, Victoria; Brandenburg, Julius; Engel, Regina; Malm, Sven; Bräuchle, Christoph; Holst, Otto; Lindhorst, Thisbe K.; Reiling, Norbert
Abstract: Mycobacterium tuberculosis (Mtb), the main causative agent of tuberculosis (Tb), has a complex cell envelope which forms an efficient barrier to antibiotics, thus contributing to the challenges of anti‐tuberculosis therapy. However, the unique Mtb cell wall can be considered an advantage and be utilized to selectively label Mtb bacteria. Here we introduce three azido pentoses as new compounds for metabolic labeling of Mtb: 3‐azido arabinose (3AraAz), 3‐azido ribose (3RiboAz), and 5‐azido arabinofuranose (5AraAz). 5AraAz demonstrated the highest level of Mtb labeling and was efficiently incorporated into the Mtb cell wall. All three azido pentoses can be easily used to label a variety of Mtb clinical isolates without influencing Mtb‐dependent phagosomal maturation arrest in infection studies with human macrophages. Thus, this metabolic labeling method offers the opportunity to attach desired molecules to the surface of Mtb bacteria in order to facilitate investigation of the varying virulence characteristics of different Mtb clinical isolates, which influence the outcome of a Tb infection. Abstract : Sugar for tuberculosis : Azido pentoses show excellent labeling of Mycobacterium tuberculosis without affecting pathogenicity in macrophages, by exploiting the unique structure of the Mycobacterium cell wall. The three developed azido pentoses could serve as robust tools for virulence studies with Mycobacterium clinical isolates.